2016
DOI: 10.15448/2357-9641.2016.1.23159
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with cognitive performance of non-demented elderly outpatients

Abstract: Objective: To evaluate the cognitive performance of non-demented elderly and its relation to sociodemographic, clinical and biochemical variables. Methods: 71 subjects (≥ 60 years) were studied. Sociodemographic data were collected in interviews; MMEM was used to assess cognition, the clinical variables were taken from the patient's medical record, and biochemical measurements were taken through blood tests which measured serum levels of vitamin B 12 , TSH and CrP. Results: Most of the subjects were women, old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The literature shows that cardiovascular diseases, especially SAH, have been associated with memory deficit, attention and abstract reasoning (5,7,9,23) . Concerning dyslipidemias, a study that showed an association with cognitive impairment was identified (28) .…”
Section: Discussionmentioning
confidence: 99%
“…The literature shows that cardiovascular diseases, especially SAH, have been associated with memory deficit, attention and abstract reasoning (5,7,9,23) . Concerning dyslipidemias, a study that showed an association with cognitive impairment was identified (28) .…”
Section: Discussionmentioning
confidence: 99%